1977
DOI: 10.1002/macp.1977.021781203
|View full text |Cite
|
Sign up to set email alerts
|

Studies on chitin, 4. Evidence for formation of block and random copolymers of N‐acetyl‐D‐glucosamine and D‐glucosamine by hetero‐ and homogeneous hydrolyses

Abstract: Chitin was deacetylated by heterogeneous and homogeneous alkaline hydrolyses. In the heterogeneous hydrolysis, upper limits in the degree of deacetylation were found to exist at low reaction temperatures. The products obtained were all insoluble in water and those with a degree of deacetylation up to 80% retained some crystallinity. These results seemed to indicate that the deacetylation under the heterogeneous conditions proceeded preferentially in the amorphous region to give block-type copolymers of N-acety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
100
1

Year Published

1990
1990
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(108 citation statements)
references
References 5 publications
7
100
1
Order By: Relevance
“…It ist herefore~considered that only GlcN around the surface of the sample particles effectively functioned in adsorbing Cu 2 +. DA-Ct-under-Homo in which all the GleN are distributed homogeneously in the molecules 8 ) may not be able to function efficiently as an adsorbent. On the other hand, DA-Ct-under-Hetero showed unexpectedly high Cu 2 + adsorption capacity, which may be due to the preferential distribution of a number of GleN on the surface of DA-Ct-under-Hetero particles.…”
Section: Comparison Of Cu 2 + Adsorption Capacity Of Fungal-cs With Tmentioning
confidence: 99%
See 1 more Smart Citation
“…It ist herefore~considered that only GlcN around the surface of the sample particles effectively functioned in adsorbing Cu 2 +. DA-Ct-under-Homo in which all the GleN are distributed homogeneously in the molecules 8 ) may not be able to function efficiently as an adsorbent. On the other hand, DA-Ct-under-Hetero showed unexpectedly high Cu 2 + adsorption capacity, which may be due to the preferential distribution of a number of GleN on the surface of DA-Ct-under-Hetero particles.…”
Section: Comparison Of Cu 2 + Adsorption Capacity Of Fungal-cs With Tmentioning
confidence: 99%
“…On the other hand, DA-Ct-under-Hetero showed unexpectedly high Cu 2 + adsorption capacity, which may be due to the preferential distribution of a number of GleN on the surface of DA-Ct-under-Hetero particles. 8 ) However, as it is unlikely that Fungal-Cs extracted from the fungal cell walls has more GleN residues on the surface of their particles than do the highly hydrophobic DA-Ct-under-Hetero, other reasons should be considered for the high Cu 2 + adsorption capacity of Fungal-Cs.…”
Section: Comparison Of Cu 2 + Adsorption Capacity Of Fungal-cs With Tmentioning
confidence: 99%
“…Moreover, it is apparent that water-solubility is influenced by the molecular weight as well as the degree of N-acetylation; lowering the molecular weight helps to improve solubility. Because it was reported that blockwise distribution of N-acetyl groups reduced the water-solubility, 8 residues was then investigated by 1 H NMR spectroscopy.…”
Section: Da(¾)mentioning
confidence: 99%
“…However, (GleNAch had not been detected in our previous study, 2 ) because oligosaccharides were isolated from the hydrolyzate after incubation for 96 hr. Kurita et al 9 l have reported that the N-deacetylation of chitin by alkali under heterogeneous condition proceeds preferentially in the ~morphous region in deacetylating chitin to give block-type copolymers consisting of GleNAc and GleN. As 25% N-acetylated chitosan used in this study was prepared by heterogeneous N-deacetylation of chitin, GleNAc residues would probably be distributed as blocks in the chitosan molecules.…”
mentioning
confidence: 83%